2014
DOI: 10.1371/journal.pone.0103106
|View full text |Cite
|
Sign up to set email alerts
|

Wind Farm Facilities in Germany Kill Noctule Bats from Near and Far

Abstract: Over recent years, it became widely accepted that alternative, renewable energy may come at some risk for wildlife, for example, when wind turbines cause large numbers of bat fatalities. To better assess likely populations effects of wind turbine related wildlife fatalities, we studied the geographical origin of the most common bat species found dead below German wind turbines, the noctule bat (Nyctalus noctula). We measured stable isotope ratios of non-exchangeable hydrogen in fur keratin to separate migrants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 27 publications
3
73
0
5
Order By: Relevance
“…In the USA, fatalities peak in mid-July through early September in most parts of the country (Johnson 2005;Arnett et al 2008;Baerwald and Barclay 2011;Arnett and Baerwald 2013). Studies from Europe demonstrate a similar pattern (e.g., in Germany, where most (about 90 %) bat fatalities at wind turbines occur between mid-July and the end of September; Brinkmann et al 2011;Lehnert et al 2014). Some studies from northern Europe and North America demonstrate smaller peaks of fatalities during spring Rydell et al 2010a).…”
Section: Temporal Patternsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the USA, fatalities peak in mid-July through early September in most parts of the country (Johnson 2005;Arnett et al 2008;Baerwald and Barclay 2011;Arnett and Baerwald 2013). Studies from Europe demonstrate a similar pattern (e.g., in Germany, where most (about 90 %) bat fatalities at wind turbines occur between mid-July and the end of September; Brinkmann et al 2011;Lehnert et al 2014). Some studies from northern Europe and North America demonstrate smaller peaks of fatalities during spring Rydell et al 2010a).…”
Section: Temporal Patternsmentioning
confidence: 97%
“…Arnett et al (2013a) noted that studies failing to demonstrate statistically significant effects could be explained by lack of treatments being implemented during the study (i.e., winds were either too low or high to enable comparison of treatments). In Portugal, a mitigation study found that estimated mortality at turbine with raised cut-in speed was 0.3 bats/turbine compared to 1.6 bats/turbine at turbines operating normally, which resulted in a 78.5 % reduction in bat fatalities assuming all turbines at the facilities had raised cut-in speed (LEA 2010).…”
Section: Mitigating Bat Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, for residents who live close to them, wind turbines have been found to have unpleasant noise emissions (see, for example, Knopper and Ollson (2011) or Shepherd et al (2011)) and, most importantly, negative impacts on landscape aesthetics (see, for example, Devine-Wright (2005), Jobert et al (2007), or Wolsink (2007)). Moreover, they have been shown to have negative impacts on biodiversity (see, for example, Lehnert et al (2014)). Just as other electricity generation technologies, thus, wind turbines do not come without negative externalities, which, in general, do not have market prices and, therefore, are typically valued monetarily using stated preference approaches (see, for example, Groothuis et al (2008), Jones and Eiser (2010), or Meyerhoff et al (2010)) or revealed preference approaches (see, for example, Dröes and Koster (2014), Gibbons (2014), or Sunak and Madlener (2014)).…”
Section: Introductionmentioning
confidence: 99%
“…Although it could seem that different bat species groups are susceptible to wind turbines in America and Europe, it should be taken into account that all migratory tree-roosting bats from America are aerial-hawking, while mortality of migratory species also occurs in Europe but in smaller proportions (64 % in NW Europe, Rydell et al 2010 ; 56 % in Greece, Georgiakakis et al 2012 ;40 % in Portugal, Amorim et al 2012 ). However, a significant proportion of migratory killed bats in Europe belong to resident populations (Lehnert et al 2014 ).…”
Section: Effects Of Solar Plants and Wind Farms On Wildlifementioning
confidence: 99%